2022
DOI: 10.3390/plants11223093
|View full text |Cite
|
Sign up to set email alerts
|

Cytoplasmic Male Sterility Incidence in Potato Breeding Populations with Late Blight Resistance and Identification of Breeding Lines with a Potential Fertility Restorer Mechanism

Abstract: Cytoplasmic male sterility (CMS) in potato is a common reproductive issue in late blight breeding programs since resistant sources usually have a wild cytoplasmic background (W or D). Nevertheless, in each breeding cycle male fertile lines have been observed within D- and T-type cytoplasms, indicating the presence of a fertility restorer (Rf) mechanism. Identifying sources of Rf and complete male sterility to implement a CMS–Rf system in potato is important since hybrid breeding is a feasible breeding strategy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…While hybrids or varieties with S. demissum -derived D-type cytoplasm usually participate in crosses with S. tuberosum as maternal parents due to unilateral incompatibility [ 21 , 74 , 75 , 76 ] or functional pollen sterility [ 29 ]. However, more data are coming about finding efficient pollinators possessing the D-type cytoplasm [ 62 , 72 , 74 , 77 ] that could possibly be explained by the presence of functional alleles of the nuclear restorer genes [ 78 , 79 ]. At the same time, the detection of the R1 gene marker is additional but not direct evidence of introgression from S. demissum because the markers of this gene have no clear phylogenetic signals; their homologous and pseudogenes were found in other potato species [ 80 , 81 , 82 , 83 ].…”
Section: Discussionmentioning
confidence: 99%
“…While hybrids or varieties with S. demissum -derived D-type cytoplasm usually participate in crosses with S. tuberosum as maternal parents due to unilateral incompatibility [ 21 , 74 , 75 , 76 ] or functional pollen sterility [ 29 ]. However, more data are coming about finding efficient pollinators possessing the D-type cytoplasm [ 62 , 72 , 74 , 77 ] that could possibly be explained by the presence of functional alleles of the nuclear restorer genes [ 78 , 79 ]. At the same time, the detection of the R1 gene marker is additional but not direct evidence of introgression from S. demissum because the markers of this gene have no clear phylogenetic signals; their homologous and pseudogenes were found in other potato species [ 80 , 81 , 82 , 83 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, future attempts to develop dihaploid lines should take cytoplasmic factors into account to increase the likelihood of success. Santayana et al ( 2022 ) recently confirmed a male fertility restoration mechanism in certain CIP breeding lines, which may prove valuable for hybrid potato breeding that makes use of CMS. Additionally, CIP has established a collaboration with private sector to enhance its capacity in deploying diploid-based breeding strategy in East-Africa.…”
Section: Breeding Approachesmentioning
confidence: 94%
“…To apply CMS efficiently in a breeding program, fertility restorer genes are important, to be able to use material freely as both male and female parent in crosses. Recently, Santaya et al, showed the presence of restorer genes in populations containing Late Blight resistance genes for different wild sources [ 52 ]. However, in the case of potato, where the tubers and not the seeds are the product, male sterile hybrids can be developed, which may have the additional advantage of leaving fewer seeds and reduce volunteers.…”
Section: Inbred Line Developmentmentioning
confidence: 99%